Extra-Ribosomal Functions of the Ribosomal Protein, RPS3 as Predicted by In Silico Analysis - Sim, Edmund U. H.; Er, Chin Ming (Universiti Malaysia Sarawak (UNIMAS), 2014)
Products of ribosomal protein (RP) genes have been found to play extra-ribosomal roles that range from DNA repair to RNA splicing. Their association with congenital disorders or cancers has also been widely documented. However, the relatively large number of different RPs, each with perhaps unique biological roles, has compounded the comprehensive elucidation of the physiological functions of each RPs. Experimental functional studies on the many and variegated RPs are labour intensive, time-consuming and costly. Moreover, experimental studies unguided by theoretically insights entail inaccurate results. Therefore, knowledge on the actual roles of these proteins remains largely undefined. A valid alternative is the use of bioinformatics resources to computationally predict functional roles of these biomolecules. Findings from such in silico studies of the RPS3 are reported herein. We reveal an array of possible extra-ribosomal functions that includes regulation of transcription (including via NF-κB-mediated, POK-induced and DNA-dependent), regulation of p53 activities and its stabilisation, inflammatory immune response, modulation of nNOS activities, and anti-oxidative capabilities. Our findings provide computational prediction of de novo extra-ribosomal functions of RPS3. These results will enhance the theoretical basis for designing future experimental studies on elucidating its definitive physiological roles.